2017
DOI: 10.1089/ars.2017.7136
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Degradation

Abstract: Glutathione degradation plays a far greater role in cellular physiology than previously envisaged. The differential regulation and differential specificities of various enzymes, each acting on distinct pools, can lead to different consequences to the cell. It is likely that the coming years will see these downstream effects being unraveled in greater detail and will lead to a better understanding and appreciation of glutathione degradation. Antioxid. Redox Signal. 27, 1200-1216.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 149 publications
0
81
0
Order By: Relevance
“…This is especially so in the light of the recent data that has emerged on glutathione degradation. A new cycle becomes apparent with these new discoveries and we refer to this as the “Glutathione cycle” (Fig. ).…”
Section: The Proposed “Glutathione Cycle”mentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially so in the light of the recent data that has emerged on glutathione degradation. A new cycle becomes apparent with these new discoveries and we refer to this as the “Glutathione cycle” (Fig. ).…”
Section: The Proposed “Glutathione Cycle”mentioning
confidence: 99%
“…Despite the elegance of the cycle, the proposed function of the cycle in amino acid transport has subsequently proved incorrect. Furthermore, new understanding on the transport of amino acids and glutathione, identification and characterization of the genes for the enzymes that were previously unidentified in the cycle, identification of γ‐glutamyl acting enzymes unlinked to glutathione metabolism, as well as discoveries of new enzymes for the degradation of glutathione, has revealed that the steps relating to the degradation of glutathione, and downstream of the initiation of degradation are now quite different from what was originally proposed . Surprisingly, the sequence of reactions and even the pictorial representation of the cycle continue to persist in many textbooks of biochemistry as well as metabolic pathway databases such as Metacyc.…”
Section: Introductionmentioning
confidence: 99%
“…GSH homeostasis is balanced by GSH biosynthesis, transport and efflux of GSH, GSH-acting enzymes, and GSH degradation [6]. Although the contribution of GSH biosynthesis has been well studied, the GSH degradation pathway, which involves the initial cleavage of GSH, remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…GSH biosynthesis and degradation are together referred to as the γ‐glutamyl cycle (Fig. S1), necessary for GSH homeostasis (Bachhawat & Kaur, ). GSH turnover in Arabidopsis is known to be rapid (Ohkama‐Ohtsu et al ., ).…”
Section: Introductionmentioning
confidence: 99%